La frontière linguistique. Des siècles d’incertitude ... - Lanneau, Catherine (Histoire des institutions diachroniques. Le pouvoir politique en Wallonie, 2022)
Keywords: Französisch; Niederländisch; Sprachgrenze; Sprachkonflikt; Sprachpolitik

La frontière linguistique en Belgique et dans le Nord de la France de Godefroid Kurth (1847–1916). Historiographie de l’origine d’une controverse - Jottrand, Maxime (Revue belge de Philologie et d'Histoire, 2017)
Aus den Verlagsangaben: „La frontière linguistique en Belgique et dans le Nord de la France of Godefroid Kurth (1847–1916). Historiography of the Origin of a Controversy. Since the publication of "La frontière linguistique en Belgique et dans le Nord de la France (1896–1898)", the Belgian study of the historical origin of the demarcation between Germanic and Romance people cannot be written without referring to this fundamental work. The author, Godefroid Kurth contributed in shaping a historical object in regards to its methodological, chronological and topographical aspects. This work takes place in a national as well as European continuum. In the second half of the nineteenth century, the definition of a national identity is conceived according to criteria considered as scientific. In this configuration, the linguistic and racial elements were strongly mobilized. Our ambition with this paper is to go back to the redaction context of Kurth’s book, and thereby understand the sources of the historical but also topographical issue of the Linguistic Frontier in Belgium.“
Keywords: Französisch; Niederländisch; Sprachgrenze; Sprachkonflikt; Sprachpolitik

De taalgrens. Of wat de Belgen zowel verbindt als verdeelt - Raskin, Brigitte (Davidsfonds, 2012)
Keywords: Französisch; Niederländisch; Sprachgrenze; Sprachkonflikt

La frontière linguistique, 1878–1963 - Rillaerts, Stéphane (Courrier hebdomadaire, 2010)
Keywords: Französisch; Niederländisch; Sprachgrenze; Sprachkonflikt